The Effect Of Financial Literacy and Digital Financial Inclusion on Business Sustainability in the MSMEs Agribusiness Sector with Financial Performance as an Intervening Variable - Pasmai Denta; Muhamad Mustopa Romdhon; Nurna Aziza (Yayasan Darussalam Bengkulu, 2026)
Background: Downstream agribusiness MSMEs play a crucial role in generating added value for agricultural products and improving regional economic development. However, these businesses face significant challenges in financial management and the utilization of digital financial technology, which can threaten their long-term sustainability. This study examines the effect of financial literacy and digital financial inclusion on business sustainability in the downstream agribusiness sector, with financial performance as an intervening variable. Method: This research employs a quantitative approach using a survey method targeting business actors in the downstream agribusiness sector in Bengkulu City. A sample of 100 respondents was selected using purposive sampling, with criteria of at least two years of business operation, direct involvement in financial management, and utilization of digital financial services such as QRIS. Data were analyzed using SEM-PLS with SmartPLS software. Results: The findings reveal that digital financial inclusion has a positive effect on financial performance and business sustainability, both directly and through financial performance mediation. Financial performance positively influences business sustainability. Financial literacy positively affects financial performance but does not directly influence business sustainability, nor does financial performance mediate the relationship between financial literacy and business sustainability. Conclusion: Digital financial inclusion plays a stronger role in improving financial performance and business sustainability compared to financial literacy alone. Strengthening the digital financial ecosystem and integrating financial literacy with practical financial management training are essential strategies for enhancing MSME sustainability in the downstream agribusiness sector.